2001
DOI: 10.1038/sj.cdd.4400805
|View full text |Cite
|
Sign up to set email alerts
|

A20 zinc finger protein inhibits TNF-induced apoptosis and stress response early in the signaling cascades and independently of binding to TRAF2 or 14-3-3 proteins

Abstract: A20 zinc finger protein is a negative regulator of tumor necrosis factor (TNF)-induced signaling pathways leading to apoptosis, stress response and inflammation. A20 has been shown to bind to TNF-receptor-associated factor 2 (TRAF2) and 14-3-3 chaperone proteins. Our data indicate that the zinc finger domain of A20 is sufficient and that neither TRAF2 nor 14-3-3 binding is necessary for the inhibitory effects of A20. Mutations in the 14-3-3 binding site of A20 did, however, result in a partial cleavage of A20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 41 publications
2
30
1
Order By: Relevance
“…A20 inhibits TNF-induced proapoptotic signaling by inhibiting both the activation of caspase 8 and the activation of c-Jun (54). However, neither the drug-induced proapoptotic mechanisms nor the A20-induced antiapoptotic mechanisms have been investigated in this study; our observation of cytotoxicity despite high antiapoptotic A20 mRNA levels may suggest an overriding mechanism.…”
Section: Discussioncontrasting
confidence: 47%
“…A20 inhibits TNF-induced proapoptotic signaling by inhibiting both the activation of caspase 8 and the activation of c-Jun (54). However, neither the drug-induced proapoptotic mechanisms nor the A20-induced antiapoptotic mechanisms have been investigated in this study; our observation of cytotoxicity despite high antiapoptotic A20 mRNA levels may suggest an overriding mechanism.…”
Section: Discussioncontrasting
confidence: 47%
“…Other studies found that GADD45b/MyD118, an NF-kB target gene that belongs to the GADD45 family of factors involved in cell cycle control and DNA repair, is involved in suppressing JNK signaling at the level of JNKK2/MKK7 (De Smaele et al, 2001;Papa et al, 2003). The NF-kB-regulated zinc-finger protein A20, which antagonizes TNF induction of JNK, is another possible contender (Lademann et al, 2001). Nevertheless, elimination of XIAP in MEFs was not sufficient to abolish inactivation of JNK by NF-kB (A Lin, personal communication).…”
Section: Crosstalk Between Nf-kb and Jnk: Something To Live Formentioning
confidence: 99%
“…More importantly, the ectopic expression of both A20 and c-IAP1 conferred significant protection against apoptosis induced by luteolin and TNFa (Figure 7). Zinc-finger protein A20 is a NF-kB inducible gene (Krikos et al, 1992) and one of its important functions is inhibition of TNFamediated apoptosis (Song et al, 1996;Lademann, et al, 2001). A20-deficient cells have been reported to be highly susceptible to apoptosis induced by TNFa (Lee et al, 2000).…”
Section: Discussionmentioning
confidence: 99%